2006
DOI: 10.1051/0004-6361:20054120
|View full text |Cite
|
Sign up to set email alerts
|

Implications of elemental abundances in dwarf spheroidal galaxies

Abstract: Unusual elemental abundance patterns observed for stars belonging to nearby dwarf spheroidal (dSph) galaxies are discussed. Analysis of the [α/H] vs. [Fe/H] diagrams where α represents Mg or an average of α-elements reveals that Fe from type Ia supernovae (SNe Ia) does not contribute to the stellar abundances in the dSph galaxies where the member stars exhibit low α/Fe ratios except for the most massive dSph galaxy, Sagitarrius. The more massive dwarf (irregular) galaxy, the Large Magellanic Cloud, also has an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 51 publications
2
5
0
Order By: Relevance
“…iii) HNe may produce even a larger amount of Fe due to a smaller fallback mass or a larger energy than the typical HNe in our yields. iv) Also SNe I.5, which are the SN Ia-like explosions of metal-poor AGB stars, have been suggested by Nomoto et al (2003) (see also Tsujimoto 2006).…”
Section: Oxygenmentioning
confidence: 77%
“…iii) HNe may produce even a larger amount of Fe due to a smaller fallback mass or a larger energy than the typical HNe in our yields. iv) Also SNe I.5, which are the SN Ia-like explosions of metal-poor AGB stars, have been suggested by Nomoto et al (2003) (see also Tsujimoto 2006).…”
Section: Oxygenmentioning
confidence: 77%
“…[Si/Fe] behaves like [Ca/Fe] and [Ti/Fe] in the Galactic bulge. Tsujimoto (2006) suggested that the low α-element signature in the dSph galaxies is a reflection of the contribution of massive stars with smaller rotation compared to solar neighborhood stars, instead of the conventional interpretation that this is a consequence of a low star formation rate. Current data are significantly better than what was available to him in 2006.…”
Section: Comparison With Other Dsph Galaxiesmentioning
confidence: 99%
“…Alternative suggestions based on different IMF (e.g. Shetrone et al 2001) or on less rotation of massive stars (compared to solar neighbourhood) have also been invoked (Tsujimoto 2006), but we do not consider here these speculative hypotheses.A glance at Fig. 9 illustrates that in our simulations a decrement of ∼0.2 dex in the plateau is achieved after t ∼ 2.0 Gyr.…”
Section: Comparison To Other Modelsmentioning
confidence: 99%